FAKTOR- FAKTOR YANG MEMPENGARUHI TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH - Sucahyo Heriningsih; Rusherlistyanti . (Fakultas Ekonomi Universitas Pekalongan, 2015)
This research is aimed to examine the influence of the characteristics and level of accountability from local government to local government financial statement disclosure. The samples numbered 46 cities andcounties are taken from the BPK, sampling using purposive sampling method and using multiple linearregression analysis. The results of the study shows that the characteristics of the local government (dependency rate and the size of the local government) and the level of accountability (the auditor's opinion, the weakness of the SPI, non-compliance with the law) does not affect the local government's financial statement disclosure. Keywords: characteristics of local government, the level of accountability of local government, local government financial statement disclosure.